Factors associated with primary multidrug-resistant tuberculosis in patients from Callao, Peru - Ávalos Rodríguez, Ana Cecilia (2014)
Introduction: Lima and Callao are high risk areas for tuberculosis active transmission in Peru. Multidrug-resistant tuberculosis represents 5.54% of the new cases of pulmonary tuberculosis (primary MDR-TB) in Lima and Callao. Involved risk factors have not been studied in patients from Callao. Objectives: To determine risk factors for primary MDR-TB in patients attending health care facilities in Callao during 2009-2010. Design: Case-control study. Setting: Health care facilities from Callao. Participants: Twenty nine primary MDR-TB patients and 37 drug-sensitive TB patients were studied through assessment of the Tuberculosis Control Program Registries and healthcare facilities’ clinical records. Interventions: Information was obtained from secondary sources. Odds-ratios were calculated by bivariate analysis. Logistic regression models were used to calculate multivariate odd-ratios. Main outcome measures: Risk factors for primary MDR-TB. Results: Prior contact with a MDR-TB or XDR-TB patient was a significant risk factor (OR: 5.56; 95%CI: 1.05-29.27) in bivariate analysis; the same was found in multivariate analysis (OR: 14.56; 95%CI: 1.52–139.54). Being 40 or more years old was a significant protective factor in multivariate analysis (OR: 0.94; 95% CI: 0.90–0.99). Conclusions: Previous contact with a MDR-TB or XDR-TB patient was a risk factor, and being 40 or more years old was a protective factor for primary MDR-TB in Callao patients studied.